2018
DOI: 10.1590/1678-5150-pvb-5122
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological, clinical and pathological features of canine parvovirus 2c infection in dogs from southern Brazil

Abstract: Canine parvovirus type 2c (CPV-2c) emerged in Europe in the early 2000’s and rapidly spread out worldwide. Clinical and molecular data have demonstrated its circulation in Brazilian dogs, yet detailed descriptions of cases are still lacking. This article describes the epidemiological, clinical and pathological features of 24 cases of CPV-2c-associated disease in dogs submitted to veterinary clinics and laboratory diagnosis in southern Brazil (2014-2016). Most affected dogs presented signs/lesions suggestive of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 29 publications
3
13
1
1
Order By: Relevance
“…Although CVP-2c has been detected in several Brazilian regions, this is the first description of its circulation in rural/wild areas representing human/wildlife interfaces ( Costa et al, 2005 ; Streek et al, 2009 ; Castro et al, 2010 ; Fontana et al, 2013 ; Oliveira et al, 2017 ). Despite of the availability and use of several commercial vaccines, viral enteritis − including that associated with CPV infection − remains an important problem for Brazilian dogs ( Oliveira et al, 2017 ). In addition, our study showed that CPV isolation is feasible when faeces are processed shortly after collection.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…Although CVP-2c has been detected in several Brazilian regions, this is the first description of its circulation in rural/wild areas representing human/wildlife interfaces ( Costa et al, 2005 ; Streek et al, 2009 ; Castro et al, 2010 ; Fontana et al, 2013 ; Oliveira et al, 2017 ). Despite of the availability and use of several commercial vaccines, viral enteritis − including that associated with CPV infection − remains an important problem for Brazilian dogs ( Oliveira et al, 2017 ). In addition, our study showed that CPV isolation is feasible when faeces are processed shortly after collection.…”
Section: Resultsmentioning
confidence: 74%
“…Sequence analysis showed that 90.2% of the samples carried the amino acid (aa) Glu at the position 426, characteristic of CPV-2c strains, and 65% of these CPV-2c strains showed the substitution. Despite of the fact that CPV-2c was first described in South America in 2007, the high prevalence of CPV-2c strains in Brazil continues nowadays ( Pérez et al, 2007 ; Streek et al, 2009 ; Calderón et al, 2015 ; Fontana et al, 2013 ; Oliveira et al, 2017 ). Out of the 67 positive samples, 10% were identified as CPV-2a (KP694304) and 7% CPV-2b (KP694306) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Враховуючи те що у більшості з доступних нам літературних джерелах наводиться вичерпна інформація щодо виражених патолого-анатомічні змін у шлунково-кишковому тракті (при кишковій формі), а головним чином у тонкому відділі кишечнику (Geetha, 2015;Mylonakis et al, 2016;D'Oliveira et al, 2018), нами була проведена робота щодо вивчення патоморфологічних особливостей впливу парвовірусу на шлунок та товстий відділ кишечнику собак, тому вважаємо, що дана інформація є актуальною і необхідною як для практикуючих лікарів ветеринарної медицини, так і для науковців.…”
Section: вступunclassified
“…CPV-2c was only isolated in 2018 from naturally infected dogs in the state of Rio Grande do Sul [6]. Given the relevance of CPV-2 as a major cause of canine enteritis, this paper reports the isolation of CPV-2c in cell culture from the feces of a naturally infected dog in the Central-West region of Brazil, followed by the determination of its whole sequence genome.…”
mentioning
confidence: 99%